Multiplex Real-Time qPCR Assay for Simultaneous and Sensitive Detection of Phytoplasmas in Sesame Plants and Insect Vectors - Ikten, Cengiz (PLoS One, 2016)
Phyllody, a destructive and economically important disease worldwide caused by phytoplasma infections, is characterized by the abnormal development of floral structures into stunted leafy parts and contributes to serious losses in crop plants, including sesame (Sesamum indicum L.). Accurate identification, differentiation, and quantification of phyllody-causing phytoplasmas are essential for effective management of this plant disease and for selection of resistant sesame varieties. In this study, a diagnostic multiplex qPCR assay was developed using TaqMan(®) chemistry based on detection of the 16S ribosomal RNA gene of phytoplasmas and the 18S ribosomal gene of sesame. Phytoplasma and sesame specific primers and probes labeled with different fluorescent dyes were used for simultaneous amplification of 16SrII and 16SrIX phytoplasmas in a single tube. The multiplex real-time qPCR assay allowed accurate detection, differentiation, and quantification of 16SrII and 16SrIX groups in 109 sesame plant and 92 insect vector samples tested. The assay was found to have a detection sensitivity of 1.8 x 10(2) and 1.6 x 10(2) DNA copies for absolute quantification of 16SrII and 16SrIX group phytoplasmas, respectively. Relative quantification was effective and reliable for determination of phyllody phytoplasma DNA amounts normalized to sesame DNA in infected plant tissues. The development of this qPCR assay provides a method for the rapid measurement of infection loads to identify resistance levels of sesame genotypes against phyllody phytoplasma disease.